Prawne uwarunkowania planowania przestrzennego wynikające z przepisów szczegółowych - Rochmińska, Agnieszka (Space – Society – Economy, 2009)
In Poland planning is regulated by Planning and Land Development Act (2003), numerous detailed regulations and execut or provisions. Approximately several dozen acts determine process of spatial planning on regional and local level. The situation is even more complicated when one realises never ending process of amendments. Taking above under consideration the author decided to present the newest acts and regulation and give critical comment on them.